2020
DOI: 10.1155/2020/8686248
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Improving Lipid Metabolism by Regulating Lipid Metabolism Pathway of Ileum Mucosa in Broilers

Abstract: This study is aimed at evaluating the regulatory mechanism of quercetin on lipid metabolism in the ileum of broilers to better understand these pathways decreasing abdominal fat. 480 chickens were randomly divided into 4 groups (control, 0.02% quercetin, 0.04% quercetin, and 0.06% quercetin). Breast muscle, thigh muscle, and abdominal fat pad were removed and weighed at 42 d of age. Serum was obtained by centrifuging blood samples from the jugular vein (10 ml) to determine high-density lipoprotein (HDL), total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 96 publications
1
12
0
Order By: Relevance
“…Beyond this, we further explored the mechanism by which quercetin improves lipid metabolism because quercetin alleviates lipid accumulation in HepG2 cells, which was also consistent with literature reports [ 31 , 48 ]. Hepatic lipid deposition is caused by an imbalance between lipogenesis and lipolysis.…”
Section: Discussionsupporting
confidence: 82%
“…Beyond this, we further explored the mechanism by which quercetin improves lipid metabolism because quercetin alleviates lipid accumulation in HepG2 cells, which was also consistent with literature reports [ 31 , 48 ]. Hepatic lipid deposition is caused by an imbalance between lipogenesis and lipolysis.…”
Section: Discussionsupporting
confidence: 82%
“…The previous study in our lab found 505 differentially expressed genes of AMPK signal pathway in the quercetin treatment, compared with the control, and the liver was the main metabolic site of lipid in broilers ( Wang et al, 2020 ); 0.04% quercetin supplementation decreased fat content of liver in laying hens ( Zhang L. et al, 2013 ). Therefore, these findings together with the present study confirmed that quercetin regulated fat metabolism, thus reduced abdominal fat deposition in broilers.…”
Section: Resultsmentioning
confidence: 83%
“…In high-fat diet (HFD) fed Wistar rats, an increase in abundance of the families Coriobacteriaceae and Enterobacteriaceae was reported that may directly alter host physiology ( Lecomte et al, 2015 ). The previous results of transcriptome sequencing showed that adenosine monophosphate activated protein kinase (AMPK) signaling pathway was the main signal pathway of lipid metabolism ( Wang et al, 2020 ). Activated AMPK pathway reduced lipid synthesis by suppressing the expression of downstream targets ( Zhao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The previous results of transcriptome sequencing showed that the AMPK signaling pathway is one of the main signaling pathways of lipid metabolism. We previously reported 505 differentially expressed genes of the AMPK signaling pathway we found in the quercetin treatments compared with the control and is the first differentially expressed gene signaling pathway ( 30 ).…”
Section: Discussionmentioning
confidence: 99%